FAKTOR RISIKO MORBIDITAS MATERNAL: DILIHAT ASPEK KUALITAS GENDER: Risk Factor Maternal Morbidty: Gender Quality Aspect - Agustin Dwi Syalfina; Nurun Ayati Khasanah; Wiwit Sulistyawati (Jurnal Ilmiah Kebidanan (Scientific Journal of Midwifery), 2019)
ABSTRACT Maternal mortality was an iceberg phenomenon caused by maternal morbidity. Maternal morbidity during pregnancy was highest in developing countries. Economic, social and cultural factors has an important role in complications of pregnancy until the death of the mother. Gender inequality in which the many roles that women have to do with men was considered an obligation of even the nature of women and often lacks protection at work even the productive role of women was less valued than the productive role of men, which causes a high incidence of complications during pregnancy, maternity and childbirth. The study aimed to analyze the effect of quality on maternal morbidity. The research design used case control with 60 cases and 60 control samples. The data used were primary data obtained through home visits and interview techniques. After that the data is analyzed by logistic regression test. The results showed that gender quality in the poor category was 17,864 times at risk of causing maternal morbidity (OR = 17,864; 95% CI = 6,021-53,001; Pvalue = 0,000). Maternal morbidity was related to women's heavy workload in managing the household and also have to make a living to cover the shortage of household income so that the working time is longer per day. The heavy workload without the husband's efforts to help reduce the workload of the mother indirectly encourages the vulnerability of the mother's body during pregnancy. Gender equality as an effort to improve gender quality has an effect on reducing the incidence of maternal morbidity. Health workers are expected to socialize about gender quality during pregnancy and increase the role of husbands in maternal health during pregnancy to postpartum.